Corporate Social Responsibility Supervisors in Indonesia: Analysis of Local Government Regulation in 10 Province in Indonesia - Diana Setiawati; Zulfiani Ayu Astutik; Soepatini soepatini; Haszmi Alfateh; Enno Haya Gladya Naranta (Fakultas Hukum Universitas Muhammadiyah Magelang, 2022)
Corporate Social Responsibility (CSR) is a business practice that is governed by the law in Indonesia. Every company in Indonesia is required to implement CSR under the Investment Law No. 25 of 2007 and the Limited Liability Company Act No. 40 of 2007. However, some local governments have created district laws that guide CSR applications because CSR rules are not officially established. In the legal concept, each regulation must appoint an institution in charge of managing and supervising the implementation of the regulation. Meanwhile, in Indonesia, every local government regulation has its own description of CSR supervisors body. Some provinces decide on the local government as a CSR supervisor, and some provinces choose district assembly as CSR supervisors. Institutional matters are stated in Law No. 11 of 2009 concerning Social Welfare, that the government and local governments coordinate the implementation of CSR. However, due to the different interpretations of each local government regulation, the legal basis for CSR supervision is unclear. So, this paper aims to know several institutions that have functions as CSR supervisors based on an analysis of regional regulations in 10 provinces in Indonesia. This research will use normative research methods, namely legal research conducted by analysing and researching library materials or secondary data. The final result of this research is policy suggestions to add an article about supervisory bodies on some regulation that regulates CSR. This research will provide insight for stakeholders that CSR supervision is very important to harmonise stakeholders and create a healthy business climate and social welfare.